Proyecto de factibilidad para la creación de una guardería infantil en el cantón Zamora, provincia de Zamora Chinchipe, para el año 2015 - Fierro Granillo, Gabriela Karina (2016)
Currently the investor to invest in a business needs to have not only capital but also studies that let you know how feasible his creation is, and how it will develop in the market. The economy of families in Ecuador and especially in the canton Zamora is basic, why it is necessary for both parents to work, creating the need to leave their children in the care of others. This existing need a business idea to the investor is created, as is the creation of a Child Development Center (CDI). This project's overall objective; determine the commercial viability of the proposal to implement the creation of a nursery in the canton Zamora, Province of Zamora Chinchipe. Next, the Materials and Methods used in this research, such as, the inductive method, deductive method, statistical method, and the analytic-synthetic method are presented; similarly, techniques are used as, Bibliographical, direct observation and survey technique. The results can be seen, the analysis and tabulation of 364 surveys of families of the canton Zamora (applicants), and 7 institutions, of which 5 are part of the Children's Centers of Good Living (CIBV), and 2 are Child Development centers (CDI) private, these results are portrayed with their respective tables and descriptive graphics. Discussion, in which emphasis was made, the four most relevant studies within an investment project, detailed below is then presented: Within the Market Study, effective demand of 5,630 children was obtained, it was also learned that the offer is of 1,848 children, thus obtaining an unmet demand for 3,782 children missing cover within the canton. The Technical Study the size of the company was determined, as well as the location, and engineering of the project, in terms of size, it was known that the nursery will have 4 classrooms with a capacity for 20 children, in which, it will host only 80 children to be served monthly, regarding the location was taken to consider the two locations macro and micro factors, since according to the application of the weighting matrix in the micro-location, the Santa Elena, street Hortensio Gómez and Second Chalco, turned out to have the highest rating compared to two other proposed options address critical weighting factors as: good location, labor, access roads or communication, transportation, physical infrastructure, proximity to customers, and basic services. In the project engineering service description presented in two types of block diagrams shown, one exclusively for the care of children from 3 months to 1 year, and one for children from 1 year to 4 years old at this point we can also appreciate the description of requirements, distribution and design facilities Nursery. In the third study, which is the Management Study, the corporate name of the company was established, taking into account its size, purpose and amount of capital. Children's nursery "Footprints" will be incorporated as a Limited Liability Company (CIA. LTDA.), Subject to the provisions established by law in this area and will be addressed by a / One Manager as legal representative for all relevant purposes exercise of their economic activities. Subsequently, the Financial Study, in which are fixed investments, deferred, and working capital, as well as the investment is $82,397.21, so the nursery can start with their economic activities is presented. In which it is to obtain funding from two types of internal and external sources, the internal source will be covered in full by the two members of the nursery with a value of $62,397.21, and the external source is the credit let's get in the National Development Bank which is 20,000.00, the budgeted costs and income are also detailed, obtaining costs for the first year of $100,165.73 and $156,995.00 income of about a Having identified the costs and revenues can find the equilibrium point, which was held for ten years of life with their respective graph, finally is the profit and loss account, which is elementary as it will help us understand what net income that is $33,910.02, as cash flow is $32,379.62 which shows inflows and outflows of cash. By the financial evaluation could analyze the economic situation of the implementation of childcare, through evaluation criteria, in order to make decisions regarding their implementation. Criteria of economic and financial assessment: - The NPV of the project is $130,292.66 greater than one positive and therefore the project is admissible. - The internal rate of return is 26.79%, higher than the rate of cost of capital is 11.83% figure, therefore, according to this criterion it can say that the project is feasible. - Regarding Benefit Cost Ratio daycare will have $1.57 cents of profit for every dollar invested. - The investment is expected to be recovered in 2 years, 5 months and 26 days, less than the life time of the project, which is 10 years, therefore, the project is feasible. - According to sensitivity analysis, it is known that the nursery supports an increase in costs of 36.36% and a decrease of its revenue from 23.22%. Within the discussion, the analysis of environmental and social impact, by the impact matrix, according to the two indicators is also: low environmental pollution and recycling of waste, according to the weighting the nursery will have a level of low positive impact, as the matrix medium positive social impact. Finally, conclusions were drawn and the result obtained after the development process and establishes final parameters on the observed, and recommendations will serve as much support as they are tips which will assess whether it is useful or not, if you will follow or reject it.